Synergistic Interactions in Microbial Biofilms Facilitate the Establishment of Opportunistic Pathogenic Fungi in Household Dishwashers - Zupančič, Jerneja; Raghupathi, Prem K.; Houf, Kurt; Burmølle, Mette; Sørensen, Søren J.; Gunde-Cimerman, Nina (Frontiers in Microbiology, 2018)
Biofilms formed on rubber seals in dishwashers harbour diverse microbiota. In this study, we focussed on the microbial composition of bacteria and fungi, isolated from a defined area of one square centimetre of rubber from four domestic dishwashers and assessed their abilities to in-vitro multispecies biofilm formation. A total of 80 isolates (64 bacterial and 16 fungal) were analysed. Multiple combinations of bacterial isolates from each dishwasher were screened for synergistic interactions. 32 out of 140 tested (23%) four-species bacterial combinations displayed consistent synergism leading to an overall increase in biomass, in all experimental trails. Bacterial isolates from two of the four dishwashers generated a high number of synergistically interacting four-species consortia. Network based correlation analyses also showed higher co-occurrence patterns observed between bacterial members in the same two dishwasher samples, indicating cooperative effects. Furthermore, two synergistic 4-species bacterial consortia were tested for their abilities to incorporate an opportunistic fungal pathogen, Exophiala dermatitidis and their establishment as biofilms on sterile ethylene propylene diene monomer M-class (EPDM) rubber and polypropylene (PP) surfaces. When the bacterial consortia included E. dermatitidis, the overall cell numbers of both bacteria and fungi increased and a substantial increase in biofilm biomass was observed. These results indicate a novel phenomenon of cross kingdom synergy in biofilm formation and these observations could have potential implications for human health.